2003
DOI: 10.1074/jbc.m212309200
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric Enzymes of Cytochrome P450 Oxidoreductase and Neuronal Nitric-oxide Synthase Reductase Domain Reveal Structural and Functional Differences

Abstract: Nitric-oxide synthases (NOSs) 1 are heme-and flavin-containing enzymes that catalyze the formation of nitric oxide (NO) and citrulline from arginine through two NADPH-requiring monooxygenation steps that are mechanistically similar, but not identical, to those of the cytochrome P450 system. NO is a molecule with diverse physiological effects, including neurotransmission, hemodynamic regulation, and cytotoxicity. There are three isoforms of NOS, neuronal (nNOS), endothelial (eNOS), and macrophage (iNOS), which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 35 publications
(39 reference statements)
2
31
0
1
Order By: Relevance
“…Separate roles for FMN and FAD in catalysis by liver microsomal NADPH-cytochrome P450 reductase and NOS (32,51,52) have already been proposed and demonstrated, so the addition of the C termini had the predicted effect. The reduction of potassium ferricyanide, however, has been shown to be mediated through the FAD domain of these enzymes (15). As a result, the addition of the shortest (iNOS) C terminus had no effect on ferricyanide reduction, whereas the addition of either the nNOS or eNOS C terminus produced minimal effects.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…Separate roles for FMN and FAD in catalysis by liver microsomal NADPH-cytochrome P450 reductase and NOS (32,51,52) have already been proposed and demonstrated, so the addition of the C termini had the predicted effect. The reduction of potassium ferricyanide, however, has been shown to be mediated through the FAD domain of these enzymes (15). As a result, the addition of the shortest (iNOS) C terminus had no effect on ferricyanide reduction, whereas the addition of either the nNOS or eNOS C terminus produced minimal effects.…”
Section: Resultsmentioning
confidence: 84%
“…The search for differences in the oxygenase domains among the different NOS isoforms led to the elucidation of the heme domain structures of all three (18,(20)(21)(22). The remarkable similarity of these structures has redirected the interest of our laboratory (14,15,(23)(24)(25) and the laboratories of others (26)(27)(28)(29) to the role of the flavoprotein domains of NOS isoforms in their intrinsic and extrinsic regulation. Because the proximal electron donor and acceptor are on the same polypeptide chain in the NOSs, and thus each potential acceptor is linked to its donor, unlike CYPOR and the cytochromes P450, regulation of electron transfer by the reductase domain is reasonable.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…for ferricyanide of 32 M, the K m of nNOS for ferricyanide is in the 1-2 mM range in the absence of CaM but is decreased by about 50% (ϳ750 M) in its presence (38). Concentrations of ferricyanide over 2 mM have very high absorbance, making it difficult to assay reduction at large enough concentrations of ferricyanide, so turnover numbers must be extrapolated from plots of initial rate versus substrate concentration, which also will yield apparent K m values.…”
Section: Resultsmentioning
confidence: 99%
“…CaM-stimulated NO synthesis and NADPH oxidation by ⌬14eNOS approach those of CaM-bound nNOS (21); thus the ⌬14-segment can be inferred to negatively control electron transfer through enzymes (36) that contributes to the relatively low catalytic activities of eNOS. Analysis of an x-ray crystal structure of the nNOS FAD domain lacking the Cterminal 22 residues (48) has revealed that the adjacent Cterminal 10 residues are disordered in the crystal structure, suggesting that the C-terminal tail probably lies between the flavins and/or between the FAD and NADPH, modulating the interflavin distance (49). As both orientation and distance between each redox partner influence the electron transfer rate, modification at the C-tail may either change the relative orientation or the distance between the two redox partners, resulting in a greater increase in electron flux.…”
Section: Discussionmentioning
confidence: 99%